Efforts To Eradicate Narcotics In The National Police: A Case Study Of Teddy Minahasa - Edi Saputra Hasibuan; Amalia Syauket (Ridwan Institute, 2023)
Narcotics are still the enemy of all civilizations around the world, this war that is still raging indefinitely takes a lot of time, energy, and thought. The real threat from the existence of narcotics clearly lurks all levels of society without exception, as well as the law enforcement of this country. The case of a National Police official, Inspector General Teddy Minahasa, is concrete evidence that no one escapes the temptation of narcotics and all the benefits provided by drug trafficking. Drug abuse and irregularities in its handling have reached an alarming stage, in this case the existence of drug evidence that was then used for resale by Teddy Minahasa who served as a two-star general, provides a new test for the National Police. This paper will highlight how legal handling through related laws and regulations, facts on the ground through case examples, and what steps have been taken by the National Police institution in suppressing and eradicating abuse and irregularities related to narcotics in their own bodies, of course this is very important considering they are law enforcers where public trust in the state is on the shoulders of this institution.